Oxygen therapy for acute myocardial infarction - Luna Filho, Bráulio (São Paulo Medical Journal, 2010)
BACKGROUND: Oxygen (O2) is widely recommended for patients with myocardial infarction yet a narrative review has suggested it may do more harm than good. Systematic reviews have concluded that there was insufficient evidence to know whether oxygen reduced, increased or had no effect on the heart ischaemia or infarct size. OBJECTIVE: To review the evidence from randomized controlled trials to establish whether routine use of inhaled oxygen in acute myocardial infarction (AMI) improves patient-centered outcomes, in particular pain and death. CRITERIA FOR CONSIDERING STUDIES FOR THIS REVIEW: The following bibliographic databases were searched (to the end of February 2010): Cochrane Central Register of Controlled Trials (CENTRAL) (The Cochrane Library), Medline, Medline In-Process, Embase, CINAHL, Lilacs and PASCAL, British Library ZETOC, Web of Science ISI Proceedings. Experts were also contacted to identify any studies. No language restrictions were applied. SELECTION CRITERIA: Randomized controlled trials of people with suspected or proven AMI, less than 24 hours after onset, in which the intervention was inhaled oxygen (at normal pressure) compared to air and regardless of co-therapies provided these were the same in both arms of the trial. DATA COLLECTION AND ANALYSIS: Two review authors independently reviewed the titles and abstracts of identified studies to see if they met the inclusion criteria and independently undertook the data extraction. The quality of studies and the risk of bias were assessed according to guidance in the Cochrane Handbook. The primary outcomes were death, pain and complications. The measure of effect used was the relative risk (RR). MAIN RESULTS: Three trials involving 387 patients were included and 14 deaths occurred. The pooled RR of death was 2.88 (95% CI 0.88 to 9.39) in an intention-to-treat analysis and 3.03 (95% CI 0.93 to 9.83) in patients with confirmed AMI. While suggestive of harm, the small number of deaths recorded meant that this could be a chance occurrence. Pain was measured by analgesic use. The pooled RR for the use of analgesics was 0.97 (95% CI 0.78 to 1.20). AUTHORS’ CONCLUSIONS: There is no conclusive evidence from randomized controlled trials to support the routine use of inhaled oxygen in patients with acute AMI. A definitive randomized controlled trial is urgently required given the mismatch between trial evidence suggestive of possible harm from routine oxygen use and recommendations for its use in clinical practice guidelines.